Evaluation of turbulent forced convection heat transfer and pressure drop of nanofluids flow in different closed conduit configurations / Ali Hassan Abdelrazek Elsayed - Ali Hassan Abdelrazek , Elsayed (2021)
Nanofluids are a relatively new class of fluids consisting of a base fluid with suspended nano-sized particles (1–100 nm). Nanofluids are suggested as a favorable convective medium because the thermal conductivity of the suspensions is typically an order-of-magnitude higher than those of normal fluids such as water. In convection heat transfer applications, some researchers reported that enhancing the convection heat transfer coefficient is directly proportional to nanofluids' thermal conductivity increment. In contrast, others said that the nanofluid thermal conductivity is not the critical parameter for enhancing convection heat transfer. Therefore, experimental and numerical work was conducted in the current study to evaluate the thermal performance of different nanofluids in different pipe geometries with the same hydraulic diameter. Three different aqua-based nanofluids of weight concentrations 0.05%, 0.075%, and 0.1% were prepared using the two-step method. One nanofluid was prepared from composite nanoparticles, composed of 60 % Al2O3 and 40% f-MWCNTs by weight. The second one was prepared from the Al2O3, and the third nanofluid was prepared from SiO2 nanoparticles. All the nanofluids showed an excellent dispersion in the stability test over one month, and their thermophysical properties were evaluated experimentally except the specific heat, which was calculated theoretically. The experimental work was conducted using a test rig containing circular and square test sections of 10 mm hydraulic diameter exposed to a uniform heat flux on their outer surfaces. The inlet flow temperature was kept constant at 30 °C in all the runs. All experimental work was done under steady-state fully developed turbulent flow conditions with the Reynolds number range of 6000-11000. The results obtained experimentally showed that the Prandtl number has the most significant effect compared to the thermal conductivity on the Nusselt number and the convection heat transfer coefficient. The numerical work was conducted to evaluate the heat transfer and pressure drop through the same geometries in the experimental work in addition to an annular heat exchanger of the same hydraulic diameter and an eccentricity range from 0.0 to 0.6. The continuity, momentum, and energy equations were solved using the finite volume approach available in the ANSYS-Fluent commercial software with the same flow and boundary conditions as the experimental work. The results obtained numerically were in good agreement with those obtained experimentally for the circular and square pipes. The annular pipe’s model was validated with some empirical correlations, shown an average error of less than 10%. All the results obtained numerically confirmed the experimental findings. Finally, the thermal performance evaluation showed that the distilled water (DW) has the highest thermal performance, and the lower nanofluid concentration has also shown the higher thermal performance. Keywords: